2007
DOI: 10.1021/jm060420k
|View full text |Cite
|
Sign up to set email alerts
|

Selective NR1/2BN-Methyl-d-aspartate Receptor Antagonists among Indole-2-carboxamides and Benzimidazole-2-carboxamides

Abstract: (4-Benzylpiperidine-1-yl)-(6-hydroxy-1H-indole-2-yl)-methanone (6a) derived from (E)-1-(4-benzylpiperidin-1-yl)-3-(4-hydroxy-phenyl)-propenone (5) was identified as a potent NR2B subunit-selective antagonist of the NMDA receptor. To establish the structure-activity relationship (SAR) and to attempt the improvement of the ADME properties of the lead, a series of compounds were prepared and tested. Several derivatives showed low nanomolar activity both in the binding and in the functional assay. In a formalin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Similar to Zn 2ϩ binding to the ATD of GluN2A (see section VI.E), ifenprodil increases the potency of proton inhibition of NMDA receptors Mott et al, 1998). Rich pharmacology exists for this site, with nearly a dozen structural classes described, including oxamides (Barta-Szalai et al, 2004), 4-(3,4-dihydro-1H-isoquinolin-2-yl)-quinolines (Bü ttelmann et al, 2003), benzamidines (Claiborne et al, 2003), 5-substituted benzimidazoles (McCauley et al, 2004), indole-2-carboxamides (Borza et al, 2006(Borza et al, , 2007, benzyl cinnamamidines (Tamiz et al, 1999;Curtis et al, 2003), and other biaryl analogs (Tamiz et al, 1998;Wright et al, 2000;Tahirovic et al, 2008;Mosley et al, 2009). …”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…Similar to Zn 2ϩ binding to the ATD of GluN2A (see section VI.E), ifenprodil increases the potency of proton inhibition of NMDA receptors Mott et al, 1998). Rich pharmacology exists for this site, with nearly a dozen structural classes described, including oxamides (Barta-Szalai et al, 2004), 4-(3,4-dihydro-1H-isoquinolin-2-yl)-quinolines (Bü ttelmann et al, 2003), benzamidines (Claiborne et al, 2003), 5-substituted benzimidazoles (McCauley et al, 2004), indole-2-carboxamides (Borza et al, 2006(Borza et al, , 2007, benzyl cinnamamidines (Tamiz et al, 1999;Curtis et al, 2003), and other biaryl analogs (Tamiz et al, 1998;Wright et al, 2000;Tahirovic et al, 2008;Mosley et al, 2009). …”
Section: E Noncompetitive Antagonistsmentioning
confidence: 99%
“…The extant literature on the synthesis and bioactivity of pyrroloindazoles revealed that eight isomeric classes of pyrroloindazoles have so far been synthesised. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Of these, only the [2,3-g]-isomers [18][19][20][21][22][23][24][25][26][27] and the [3,2-e]-isomers 22,24,25 display various biological activities. Thus, the [2,3-g]-isomers 1-4 and the [3,2-e]-pyrroloindazole 5 were bioactive.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the [2,3-g]-isomers 1-4 and the [3,2-e]-pyrroloindazole 5 were bioactive. While 1 showed analgesic and antiinflammatory activity, 18 2 showed NMDA (N-methyl D-aspartate)-receptor antagonistic property with potential for the treatment of neuropathic pain, 22 3 and 4 displayed inhibition of sGC (soluble guanylate cyclase) with potential for treating hypertension 23 whereas 5 proved to be an antagonist of NMDA-receptor. Among these two classes of pyrroloindazoles, only the [2,3-g]-types have already been subjected to rather thorough synthetic investigations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations